The ambiguous sea level rise at Brest’s 212 yearlong record elucidated - İz H. Bâki (Sciendo, 2021)
The tide gauge record at Brest, France, along Eastern part of Atlantic coast is one of the longest records in Europe spanning 212 years (1807–2019). Analyzing these records has important ramifications in assessing anthropogenic impact of climate change at local and regional scales during this period. All the previous studies that analyzed Brest’s tide gauge record have used vaguely defined quadratics models and did not incorporate the effect of sea level variations at various frequencies, which confounded the presence or absence of a plausible uniform acceleration. Here, we entertained two competing kinematic models; one with a uniform acceleration representing 212 years of monthly averaged tide gauge data, the other is a two-phase trend model (Phase I is 93 years long and Phase II is 119 years long). Both models include statistically significant (α = 0.05) common periodic effects, and sub and super harmonics of luni-solar origin for representing monthly averaged sea level anomalies observed at Brest. The least squares statistics for both models’ solutions cannot distinguish one model over the other, like earlier studies. However, the assessment of Phase I segment of the records disclosed the absence of a statistically significant trend and a uniform acceleration during this period. This outcome eliminates conclusively the occurrence of a uniform acceleration during the entire 212-year data span of the tide gauge record at Brest, favoring the two-phase trend model as a sound alternative.